SARS-CoV-2 transmission dynamics in bars, restaurants, and nightclubs - van der Veer, Brian M. J. W.; Gorgels, Koen M. F.; den Heijer, Casper D. J.; Hackert, Volker; van Alphen, Lieke B.; Savelkoul, Paul H. M.; Hoebe, Christian J. P. A.; Dingemans, Jozef (Frontiers in Microbiology, 2023)
Background In an attempt to control the spread of SARS-CoV-2, many governments decided to close public venues including bars, restaurants and nightclubs during the pandemic, making it difficult to study how transmission occurs in these environments. In this study, we were able to gain insight into the transmission dynamics of SARS-CoV-2 in 16 venues in the city of Maastricht using a combination of epidemiological and whole genome sequencing (WGS) data during a period of two weeks in 2021, when bars, restaurants and nightclubs were temporarily reopened in the Netherlands. This lead to a subsequent rise on SARS-CoV-2 cases in the community following the reopening. Methods WGS was performed on samples from 154/348 of selected cases and combined with epidemiological investigation (e.g. contact tracing and linking cases to specific venues) to identify SARS-CoV-2 transmission clusters. In addition, genomic surveillance data was used to investigate spillover of outbreak-associated genotypes into the community. Results Clustering was observed in 129/136 (95%) successfully genotyped samples. We established that most cases were linked to venues with dancing facilities and that specific genotypes of the Delta variant were more frequently spread within and from these venues compared to venues without dancing facilities. In addition, we show indications of spillover of certain genotypes from the bar and restaurant industry into the community, with the number of hospital admissions increasing in the weeks following peak cases in the community. Conclusions Lifting restrictions on bar and restaurant industry venues with a corona entree ticket in a largely unvaccinated population led to a surge in COVID-19 cases and promoted the spread of new (sub)variants. Nightclubs were identified as potential super-spreading locations.